Absolute normalized norms in R^2 and Heinz means constant - Zuo, Zhan-fei; Huang, Yi-min (Topological Methods in Nonlinear Analysis, 2022)
In this paper, we calculate the precise values of the Heinz means constant under the absolute normalized norms in R^2. The conclusions do not only contain some previous results, but also give the exact values of the Heinz means constant for some new concrete Banach spaces.